Pendampingan Sanitasi Total Berbasis Masyarakat melalui Gerakan Toilet Sekolah Ramah Anak di SD Muhammadiyah Balayuda Palembang - Zairinayati, Zairinayati (IKesT Muhammadiyah Palembang, 2024)
Healthy schools are something that is very necessary in creating a healthy and strong generation, one of which is toilet conditions. Adequate toilets, both in terms of number, appearance and facilities, have a significant impact on students' psychology. The aim of this community service is to increase school students' knowledge of using toilets and create child-friendly toilets. The implementation method is carried out by counseling using poster media and evaluation to determine the success of education for school children. At the end of the activity, the service team provided equipment for the school toilet, namely trash boxes with lids, hand washing soap, toilet tissue and slippers. The results of the activity were carried out on November 18 2023 in the Muhammadiyah Balayudha High School building in Palembang, attended by 20 grade 11 students. The material presented outlined 10 indicators of healthy toilets in terms of number, appearance and facilities including clean, bright, available tissue and soap, fragrant, dry, available running water, not slippery, available trash box, larva-free water tank. Participants were enthusiastic about taking part in this activity because each class in their school was equipped with toilet facilities. The conclusion of this activity is good information and input for the school in maintaining student health, it is necessary to pay attention to aspects of toilet cleanliness and comfort.